Resilience and Personal Improvement of Students with Motor Disabilities - Zambrano, Ruth Leonor Bergmann; Villamil, Kasandra Vanessa Saldarriaga; Cantos, Kenia Liceth GarcÃƒÂa (International Research Journal of Management, IT & Social Sciences, 2018)
The condition of disability causes multiple changes in the life of a person, putting into play different mechanisms that allow him to adapt to the new situation and learn to live with important restrictions that require an effort to realize a normalized life, in a society where there is no shortage discriminatory and differentiating attitudes, which make the process of adaptation to society more difficult, all this influences the efforts to achieve the personal improvement of the disabled and the strengthening of their resilient posture. The objective of the research is to establish the resilience and personal improvement of students with disabilities in the Universidad TÃ©cnica de ManabÃ. The research shows an analysis of the functional and conceptual background of the phenomenon related to motor disability and the rights of people who suffer from it to develop their social skills to obtain a profession. It addresses the concept of resilience and what is related to the ability of people with disabilities to overcome. The results obtained in the application of the SV-RES test prepared by the researchers (Saavedra & Villalta, 2008a), to the students who suffer motor disability and who are enrolled in different careers of the technical university of ManabÃ, are offered. Offer in tables and an analysis related to the resilience and personal improvement of said students is presented.